21st Century Skills: The Perspective of Chemistry Teachers in Indonesia - Nur Candra Eka Setiawan; Daratu Evina Kusuma Putri; Siti Marfu'ah; Indah Nur Pramesti; Mohd Shafie Rosli (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The 21st century provides many changes and challenges for teachers and students. The rapidly developing digital era broadly impacts learning development in Indonesia. The Ministry of Education and Culture of the Republic of Indonesia has promoted the implementation of an merdeka curriculum which provides flexibility for teachers to develop students' 21st century abilities. The new merdeka curriculum was established so that teachers are still adapting to these changes. This article reviews the perspectives of chemistry teachers on 21st-century skills that have developed in Indonesia. The research method used is descriptive qualitative with surveys, questionnaires, and interviews. Respondents were Chemistry teachers, totaling eighty-four teachers and scattered throughout Indonesia. Interviews followed this up with ten teachers deliberately selected from the overall sample. The results showed that 94% of Chemistry teachers understand the importance of 21st-century skills. The study reveals that optimizes 21st-century skills. Several ways can be taken, namely, using constructivist learning methods to improve skills, providing engaging learning media, making motivational learning videos, and providing more time for students to complete problem-based learning or projects. They mentioned several challenges that hindered them from applying 21st-century skills in their teaching practice. The reasons for time constraints and concerns about teaching chemistry concepts were not completed according to schedule; the assessment needed to be more optimal because it was still focused on written tests and limited resources and infrastructure. Despite the many challenges, most teachers are still keen to implement learning that applies 21st-century skills in their classes.